Review on development of external steel-confined concrete. (30th June 2019) - Chin, Chee-Loong; Ma, Chau-Khun; Tan, Jia-Yang; Ong, Chin-Boon; Awang, Abdullah Zawawi; Omar, Wahid
Highlights: Research conducted on external steel-confined concrete are discussed. Variables of structural performance of steel-confined concrete are summarised. Closed-form expressions for steel-confined concrete are reviewed. Finite element analysis models for confined concrete are critically reviewed. Abstract: Steel is a cheaper and more environmentally friendly alternative to externally confine concrete compared to the commonly known fiber-reinforced polymer (FRP). Numerous studies have been conducted both experimentally and analytically to understand the compressive behaviour of external steel-confined concrete. This paper presents an overview of four external steel-based confinement techniques for concrete followed up by review on existing closed-form expressions and finite element analysis models for external steel-confined concrete. It is shown that the four techniques can be generalised based on the strengthening mechanisms involved. Through this review, it is shown that effect of pre-load and pre-tension have not been taken into account by most previous research. Additionally, the parameters calibration for existing finite element analysis models were based on FRP-confined concrete experimental data only. The needs for future experimental investigation and analytical work for external steel-confined concrete are presented in the last part of this paper.